A evolução da indústria brasileira de fundos de investimentos de 2004 a 2009: da estabilidade à instabilidade - Itikawa, Tatiana Matie (2010)
Since the implementation of Plano Real, Brazilian s economy has been getting significant changes that have brought stability and sophistication to the financial system. In addition, since 2004, the Brazilian s investment funds industry has been going through regulatory changes that made it corresponds to 30% of GDP and is the 6th largest in the world. Based on the theory of financial instability hypothesis of Hyman Minsky, we intent to analyze the Brazilian investment funds from 2004 to June 2009: a period when the Brazilian economy shifts from stability to instability